5,7-Dihydroxyflavone acts on eNOS to achieve hypotensive effects in spontaneously hypertensive rats - Zi-Han Shen; Tongjie Ye; Baozhen Chen; Congchao Wan; Xiaolin Lu; Ting-Hsu Chen; Shuang Lin; Jia-Xin Ye; Liping Xie; Yaw-Syan Fu (Scientific Reports)
Abstract Hypertension is one of the most serious chronic diseases. This study will focus on the systemic antihypertensive mechanisms of 5,7-dihydroxyflavone from in silico simulations to in vivo validations. In-silico studies were applied by network pharmacology, molecular docking, and molecular dynamic simulation. Based on the information of network pharmacology, 5,7-dihydroxyflavone could act on several different blood pressure regulating pathways, molecular docking results confirmed it might direct binding on the active pocket of eNOS, and the average molecular distance between 5,7-dihydroxyflavone -eNOS is less than 0.4 Å by molecular dynamic simulation. The in vivo studies were carried by SHRs oral administrated with 10 mg/kg 5,7-dihydroxyflavone that could alleviate hypertensive symptoms within 30 min, but if SHRs pretreated with L-NAME (10 mg/kg, an eNOS inhibitor) can erase the anti-hypertensive effects of 5,7-dihydroxyflavone, but no affected by aminoguanidine pretreatment (100 mg/kg, the selective antagonist of iNOS). Furthermore, oral administration of 5,7-dihydroxyflavone does not affect the heart rate and pulse pressure difference in SHR rats. In conclusion, the effects of 5,7-dihydroxyflavone on blood pressure regulation may act on eNOS as an agonist to achieve its acute antihypertensive effects. These acute antihypertensive effects suggest that 5,7-dihydroxyflavone has the potential to be a candidate medication for urgently lowering blood pressure requirements without posing hypertensive risks.